Effect of International Fund for Agricultural Development (IFAD) on Community-Based Development Programme on Rural Livelihood in Katsina State, Nigeria - M., Muntaka; M., Ibrahim; A., Ali (International Journal of Environment, Agriculture and Biotechnology, 2024)
Rural development is a veritable tool for fighting poverty and achieving economic prosperity at the grassroots level. The major thrust of this study was to examine the effect of IFAD Community-Based Agricultural and Rural Development Programme on Rural Livelihood in Katsina State, Nigeria. Specifically, the study described the socio- economic characteristics of respondents; identified and described the basic infrastructure provided; determined the effect of infrastructure provided on livelihood of respondents; determined the satisfaction level with the infrastructure provided in the communities and identified and described the constraints to effective performance of IFAD-CBARDP in the study area. A structured questionnaire was used to elicit primary data from 278 respondents. Secondary data were the baseline data of IFAD-CBARDP. Descriptive and inferential statistics (t-test) were utilized for analyses. The findings revealed that, majorities (51%) of respondents were males, with average age of 40 years. About 97% were married, having a household size of between 5-10 persons, with about 68% of the respondent having an educational attainment of primary and secondary school. The result revealed that IFAD-CBARDP had impacted significantly (P 0.1) on the income of respondents at 10% level of probability. The programme had also recorded an increase in the number of assets and employment opportunities provided, after the first phase of the Programme implementation. Satisfaction level of respondents with the infrastructure provided was generally satisfactory. Nevertheless, low level of awareness, cultural factors and inadequate capital were the major constraints to effective performance of the Programme. It is therefore recommended that IFAD-CBARDP should be replicated in other Local Government Areas of the State for wider livelihood improvement. Programme planners and implementers should intensify awareness creation among rural dwellers and adopt the use of Community Driven Development approach (CDD) in the execution of Rural Development projects with poverty alleviation thrust as in the case of IFAD-CBARDP.